Establishment of human sperm-specific voltage-dependent anion channel 3 recombinant vector for the production of a male contraceptive vaccine (Faculty of Medicine Universitas Indonesia, 2012)
Background: The aim of this study was to construct a recombinant vector of human sperm specific VDAC3 gene for production of VDAC3 antibody, which is potential as male contraception vaccine. Methods: Target fragment sequence of VDAC3 gene was obtained through amplification of human sperm VDAC3 cDNA with primers covering exon 5 to exon 8. Its PCR product in size of 435 bp was cloned to the pET101/D-TOPO expression vector (5753 bp). E. coli bacteria were transformed with this vector. Cloning of VDAC3 fragment gene to the vector was confirmed by the using of XbaI restriction enzyme and PCR colony method with primers covering exons 5-8 of the human VDAC3 gene. Results: Alignment analysis of amplified fragment covering exon 5 to exon 8 of VDAC3 gene showed 94% homology to human VDAC3 gene from databank. After cloning to the expression vector and transformation to E. coli competent cells, twelve colonies could grow in culture media. Gel electrophoresis of sliced VDAC3 recombinant vector showed a single band in the size of 6181 bp in 8 colonies. After application of PCR colony and amplicon sequencing, the result showed a single band in the size of 435 bp and fragment sequence with 94% identity to human VDAC3 gene. Conclusion: The construction of human sperm specific VDAC3 gene recombinant vector was established in this study. In the future, this recombinant vector will be used to produce VDAC3 antibody for the development of a male contraception vaccine. (Med J Indones. 2012;21:61-5)